Endocrine and Bone Complications in β-Thalassemia Intermedia: Current Understanding and Treatment. (5th March 2015) - Inati, Adlette; Noureldine, MohammadHassan A.; Mansour, Anthony; Abbas, Hussein A.
Abstract : Thalassemia intermedia (TI), also known as nontransfusion dependent thalassemia (NTDT), is a type of thalassemia where affected patients do not require lifelong regular transfusions for survival but may require occasional or even frequent transfusions in certain clinical settings and for defined periods of time. NTDT encompasses three distinct clinical forms: β -thalassemia intermedia ( β -TI), Hb E/ β -thalassemia, and α -thalassemia intermedia (Hb H disease). Over the past decade, our understanding of the molecular features, pathophysiology, and complications of NTDT particularly β -TI has increased tremendously but data on optimal treatment of disease and its various complications are still lacking. In this paper, we shall review a group of commonly encountered complications in β -TI, mainly endocrine and bone complications.